HUBUNGAN ANTARA PENGUASAAN KONSEP FISIKA DAN KREATIVITAS DENGAN KEMAMPUAN MEMECAHKAN MASALAH PADA MATERI POKOK LISTRIK STATIS - Bajongga Silaban (LPPM Universitas Negeri Medan, 2014)
This research are aimed to know what was the correlation between mastery of physics concepts with problem-solving ability, creativity with problem-solving ability and. mastery of physics concept and creativity with problem-solving ability on statics electricity on SMA Nasrani 1 Medan. The samples are students of class XII IPA who had studied a statics electricity as subject consisted of 25 students were selected using purposive random sampling. The type of research is a correlation research by mastery of physic concept and creativity as an independent variable and problem-solving ability as a dependent variable. The data of mastery of physics concept and problem-solving ability were gathered by using subjectif test, meanwhile the data of creativity was gathered by using the questionnaires. Based on results of data analysis be obtained that mastery of physic concept and problem- solving ability be good-classified, meanwhile the student’s creativity be medium-classified and problem-solving ability be best-classified. Furthermore based on the test of linier regression between mastery of physics concepts with problem-solving ability and creativity with problem-solving ability be obtained regression equation are Y = 0.992X1 + 5.369 for F = 34.771 and Y = 0.523X2 + 41.77 for F = 27.291, respectively. Where as multiple regression equation between of mastery of physics concepts and creativity simultaneously with problem-solving ability is Y = 0.694X1 + 0.296X2 + 6.487 for F = 27.291 which was indicated that its regession linear. The correlation coefficients between mastery of physics concepts with problem-solving ability and creativity with problem-solving ability are r(x1, y)= 0.776 and r(x2, y)= 0.763 and based on t-test be obtained are t1= 5.893 and t2 = 4.947 for the sig. (p value) < 0.05, respectively, meanwhile the coefficient of multiple correlation between mastery of physics concepts and creativity simultaneously with problem-solving ability is (Rx1x2, y) = 0.844 and based on t-test be obtained t1= 3.866 and t2 = 2.918 for sig. (pvalue) < 0.05. The conclution of hypothesis, there are strength of positif correlations which is significant between mastery of physics concept with problem-solving ability, creativity with problem-solving ability, and mastery of physics concepts and creativity simultaneously with problem-solving ability on the subject of statics electricity for class XII IPA SMA Nasrani 1 Medan. .Kata kunci: mastery of physics concepts, creativity, ability of problem solving, statics electricity, .